SYNTHESIS AND CHARACTERIZATION OF ACTIVATED CARBON FROM MALAPARI PRESS CAKE, MALAPARI SHELL, AND CASSAVA PEEL - A'yuni, Sayida Ma'wa; Kumila, Biaunik Niski; Tjahjono, Arif (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
Activated carbon is increasingly used in various applications, prompting researchers to innovate by utilizing biomass as a source for activated carbon. This study used biomass waste from malapari press cake, malapari shell, and cassava peel. The process involved carbonizing the samples at 500°C for 2 hours, chemical activation using a 65% (w/v%) KOH solution at a 1:4 ratio, stirring with a magnetic stirrer at 120°C and 300 rpm for 2 hours, followed by physical activation at 550°C for 1 hour, and BET & SEM-EDS testing. Based on the BET test results, the surface area of the samples increased overall between pre- and post-activation. The highest increase in surface area occurred in cassava peel, which increased from 7.916 m²/g to 294.303 m²/g. Meanwhile, the malapari press cake increased from 3.122 m²/g to 11.445 m²/g, and the malapari shell increased from 12.773 m²/g to 105.320 m²/g. SEM-EDS characterization revealed that cassava peel contained the highest carbon content at 67.02%, and after activation, each sample exhibited porous surfaces, uneven textures, and various pore shapes. ImageJ software analysis showed cassava peel had the smallest pore size at 123.209 nm, compared to malapari press cake at 234.721 nm and malapari shell at 217.419 nm. These results indicate that samples with larger surface areas tend to have smaller average pore sizes.